Serological prevalence of toxoplasma gondii infection in cats (Belém, Pará, Brazil) - Rocha, Katarine de Souza; Lima, Michele de Souza; Monteiro, Thamillys Rayssa Marques; Honorio, Betsy Emely Tavares; Pinho, Ana Paula Vilhena Beckman; da Paz, Giselle Souza [UNESP]; Scofield, Alessandra; Cavalcante, Gustavo Góes; Magalhães-Matos, Paulo Cesar; Sampaio Junior, Francisco Dantas; Abel, Isis; Langoni, Helio [UNESP]; et al. (FapUNIFESP (SciELO), 2020)
We evaluated the prevalence of anti-Toxoplasma gondii antibodies in the serum samples collected from domestic cats in Belém, Pará, Brazil. We also correlated the presence of T. gondii antibodies with environmental variables and cat-owner habits. Four-hundred and forty-seven serum samples from domestic cats were analyzed. The sera were tested using an indirect immunofluorescence assay. Among the animals analyzed, 21.92% (98/447) were seropositive. A statistically significant association was found in relation to age and serology among the animals over 1 year old (p<0.01): in the group up to 1 year old, 12.82% (20/156) of the animals were positive, and in the group over 1 year old, 26.80% (78/291) were positive. Our results show that the cats in Belém, Pará region have anti-T. gondii antibodies, and their owners are not aware of toxoplasmosis or how to prevent its transmission.
Prevalência sorológica de infecção por toxoplasma gondii em gatos (Belém, Pará, Brasil)
Keywords: Feline; IFA; Toxoplasmosis